(untitled) (KULT_online, 2016)
The book maps out the dynamics of the relationship between Russia, Ukraine, Belarus, the European Union (EU) and Europe throughout the post-Soviet period. The aim is to demonstrate how competing perceptions of the EU coupled with self-images vis-à-vis Europe shape foreign policy preferences and directions in these three states. The discourses of Europe among political elites and the general public constitute the main focus of this study. By developing categories of ’Europeanness’ that prevail in contemporary public space, the book poses new questions and provides valuable perspectives for those concerned with the international relations in the post-Soviet Europe and beyond that.